2013
DOI: 10.1080/14685248.2013.780128
|View full text |Cite
|
Sign up to set email alerts
|

Third-order statistics and the dynamics of strongly anisotropic turbulent flows

Abstract: Anisotropy is induced by body forces and/or mean large-scale gradients in turbulent flows. For flows without energy production, the dynamics of second-order velocity or second-order vorticity statistics are essentially governed by triple correlations, which are at the origin of the anisotropy that penetrates towards the inertial range, deeply altering the cascade and the eventual dissipation process, with a series of consequences on the evolution of homogeneous turbulence statistics: in the case of rotating tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 57 publications
4
21
0
Order By: Relevance
“…Eddy-damping terms are kept isotropic, as done in previous EDQNM studies, [36][37][38] which showed that this was a reasonable assumption in the absence of rotation, which is the case here. More details about this assumption are given in Appendix 1, and such a choice presents also the advantage of not including new free parameters in the model.…”
Section: Anisotropic Edqnm Modellingmentioning
confidence: 96%
See 1 more Smart Citation
“…Eddy-damping terms are kept isotropic, as done in previous EDQNM studies, [36][37][38] which showed that this was a reasonable assumption in the absence of rotation, which is the case here. More details about this assumption are given in Appendix 1, and such a choice presents also the advantage of not including new free parameters in the model.…”
Section: Anisotropic Edqnm Modellingmentioning
confidence: 96%
“…Consequently, there is no guarantee that this model would work for rotating mean flows for instance: indeed, such a configuration involves turbulent waves which alter the third-order correlations. [37] Therefore, further investigations are needed, especially to fully understand the impact of rotation on the eddy-damping terms and its consequences on the RTI process.…”
Section: Modelling Of the Pressure-strain Tensor (S)mentioning
confidence: 99%
“…The derivation of the above expressions may be found in Cambon et al (2013), but with an error of sign in front of the rotation terms in (2.13). The nonlinear transfer terms on the right-hand sides of (2.12) and (2.13) are obtained by applying the (E , Z) decomposition to the transfer term T ij (k, t) in (2.3): 16) where the tensor τ ij (k, t) is defined by equations (2.5) and (2.6).…”
Section: The (E Z) Decompositionmentioning
confidence: 99%
“…A more general representation, say (E , Z, H )(k, t), first introduced by Cambon & Jacquin (1989), also includes a helicity contribution generated by a helicity spectrum H (k, t). The helicity spectrum, which is associated with the imaginary part ofR ij (k, t), is not considered here because it remains zero in homogeneous turbulence if it is not initialized or forced, usually in an unphysical way (see also the trivial helicity equation in Cambon & Jacquin (1989) and Cambon et al (2013)). In addition to their mathematical origin, the recourse to the two different terms E (k, t) and Z(k, t) has physical meaning.…”
mentioning
confidence: 99%
“…the so-called structure functions [7]. Indeed, the behavior of the higher order moments of small-scale fluctuations in turbulent flows has been the subject of both numerical and experimental studies for decade [8][9][10][11][12][13][14][15]. It is crucial to realize that not all possible structure functions are sensitive to anisotropy in the same way.…”
Section: Introductionmentioning
confidence: 99%